Rebound ebook - Alexander, Kwame (Crossover, 2018)
From the New York Times bestselling author Kwame Alexander comes Rebound, the dynamic prequel to his Newbery Award–winning novel in verse, The Crossover. Before Josh and Jordan Bell were streaking up and down the court, their father was learning his own moves. Chuck Bell takes center stage as readers get a glimpse of his childhood and how he became the jazz music worshiping, basketball star his sons look up to. A novel in verse with all the impact and rhythm readers have come to expect from Kwame Alexander, Rebound goes back in time to visit the childhood of Chuck "Da Man" Bell during one pivotal summer when young Charlie is sent to stay with his grandparents where he discovers basketball and learns more about his family's past. This prequel to the Newbery Medal- and Coretta Scott King Award-winning The Crossover scores.